Standard of Care for Blasting Negligence - Timothy Stark (International Society of Explosives Engineers, 2003)
Blasters are usually strictly liable for injury or damage caused by flyrock (trespassory invasion) and blast-induced vibrations (non-trespassory invasion). The application of strict liability to non-trespassory invasions has resulted in significant litigation that has hampered the use of blasting and the blasting industry. Stark (2002) proposes that blasters should not be held strictly liable for non-trespassory invasions but should be liable only if their conduct is proven to be negligent. This change in legal standard was proposed because improvements in blasting technology over the last thirty years allow blasting to be conducted without substantial risk of harm to property and thus the amount of harm imposed by a blast can be related to the level of care exercised by the blaster. It is anticipated that a negligence standard will reduce the amount of litigation because a plaintiff will have a greater burden to overcome. To facilitate the acceptance of a negligence standard by a court of law, this paper summarizes the standard of care using the 1977 Surface Mining Control and Reclamation Act, extensive U.S. Bureau of Mines research, and current blasting techniques, such as blasting mats. It is important for the blasting industry to promulgate a standard of care so a judge can feel confident that blasting can be routinely and systematically controlled and if the legal standard is changed from strict liability to negligence a subsequent judge or jury will be able to evaluate the level of care exercised by the blaster. This paper also suggests that the industry and/or ISEE develop and disseminate a comprehensive standard of care that courts can use to further justify a change from strict liability to negligence and evaluate the standard of care.